Taking law seriously : essays in honour of Peter Cane - Goudkamp, James; Lunney, Mark; McDonald, Leighton (London [England] : Hart Publishing, 2021)
"This book celebrates the scholarship of Peter Cane, who is one of the world's leading legal scholars of the present age. The significance and scale of his contributions to learning regarding the law over the last half-century cannot be overstated. The very high standing of his work is reflected both in the extent to which other academics have engaged with it, and the regard in which it is held by the senior judiciary in several countries. In an era of increasing specialisation among lawyers, Cane stands out on account of the unusually broad scope of his interests, which extend to both private and public law in equal measure. This substantive breadth is combined with remarkable doctrinal, historical, comparative and theoretical depth. This book is comprised of essays written by admirers of Cane's scholarship. The essays probe a wide range of issues, especially in administrative law and tort law, that have long concerned him. Consistently with the international prominence that Cane's research has enjoyed, the contributors are drawn from across the common law world. Their essays will be of value to anyone who is interested in Cane's unique contribution to private and public law scholarship."--
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Cane, Peter, -- 1950- -- Criticism and interpretation; Administrative law -- Great Britain; Civil rights -- Great Britain; Private / Civil law: general works; Electronic books.James Goudkamp, Mark Lunney, Leighton McDonald